Biocomputing 2021 2020
DOI: 10.1142/9789811232701_0002
|View full text |Cite
|
Sign up to set email alerts
|

Selection of trustworthy crowd workers for telemedical diagnosis of pediatric autism spectrum disorder

Abstract: Crowd-powered telemedicine has the potential to revolutionize healthcare, especially during times that require remote access to care. However, sharing private health data with strangers from around the world is not compatible with data privacy standards, requiring a stringent filtration process to recruit reliable and trustworthy workers who can go through the proper training and security steps. The key challenge, then, is to identify capable, trustworthy, and reliable workers through high-fidelity evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…We are able to derive accurate diagnoses through feeding the crowd workers’ responses into a machine learning classifier. However, the recruitment of the crowd workforce was a crucial part of the process, as prior studies have shown that most crowd workers do not perform particularly well at labeling behavioral features from unstructured videos (54-56).…”
Section: Discussionmentioning
confidence: 99%
“…We are able to derive accurate diagnoses through feeding the crowd workers’ responses into a machine learning classifier. However, the recruitment of the crowd workforce was a crucial part of the process, as prior studies have shown that most crowd workers do not perform particularly well at labeling behavioral features from unstructured videos (54-56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these techniques may compromise the privacy of participants by providing annotators with access to video footage, although some methods have been developed to address privacy concerns with crowdsourced annotations. 22,23…”
Section: Manual Annotation Methodsmentioning
confidence: 99%
“…can serve as a data acquisition tool and aggregate emotive videos for autism research that can be used to train a more effective automatic emotion recognition platform. The use of data collected from mobile devices, such as the built-in camera, allow for continuous phenotyping and repeat diagnoses in home settings [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. This motivates the development of a new emotion classifier designed specifically for pediatric populations, trained with images crowdsourced from Guess What?.…”
Section: Guess What? Incorporates Two Teaching Methods Based On Aba Principles: Discrete Trialmentioning
confidence: 99%